A test of Allen’s rule in subterranean mammals: The genus Ctenomys (Caviomorpha, Ctenomyidae) - Bidau, Claudio Juan (2011)
We tested the applicability of Allen’s rule in 47 species and 32 unnamed forms (populations that are probably good species or undefined taxa within a superspecies or species group) of the South American subterranean Hystricomorph rodents of the genus Ctenomys (tuco-tucos) (Rodentia: Ctenomyidae) by analyzing tail length in relation with head and body length, and body mass. Tail length allometry was analyzed by Reduced Major Axis regression while the possible correlation of relative tail length with temperature, precipitation and evapotranspiration variables was explored through Simultaneous Autoregression to account for spatial autocorrelations. Our results indicate that tuco-tucos do not follow Allen’s rule but its converse, tail proportion relative to body mass increasing with latitude while body size decreases in the same direction (the trend is similar for tail length relative to head and body length but not statistically significant). Regarding climatic variables, the main predictors of relative tail length were temperature and evapotranspiration variables with trends confirming the positive (non-Allenian) correlation of relative tail length with latitude. We conclude that tuco-tucos, being almost fully subterranean, thermoregulate behaviorally by maintaining constant temperatures within their burrows independent of geographic location. The former confirms previous results that indicated that Ctenomys follows the converse to Bergmann’s rule. Relative tail length variation would be a result of simple allometric growth.